2017
DOI: 10.1016/j.ultrasmedbio.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Cavitation Ultrasound with Microbubbles Improves Reperfusion Efficacy When Combined with Tissue Plasminogen Activator in an In Vitro Model of Microvascular Obstruction

Abstract: We have previously shown that long tone burst high mechanical index ultrasound (US) and microbubble (MB) therapy can restore perfusion in both an in vitro and in vivo model of microvascular obstruction (MVO). Addition of MB to US has been shown to potentiate the efficacy of thrombolytics on large venous thrombi, however the optimal US parameters for achieving microvascular reperfusion of MVO caused by microthrombi, when combined with tissue plasminogen activator (tPA) are unknown. We sought to elucidate the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…More importantly, US+MB treatment decreased the percentage of microthrombi-occluded myocardial arterioles, as indicated by systemic histologic analysis of postmortem myocardium. These findings indicated that MB-mediated sonothrombolysis could efficiently dissolve coronary microthrombi, which is partially supported by previous in vivo and in vitro studies ( 20 22 , 29 ). Additionally, it is widely accepted that the burden of thrombotic microemboli is highly predictive of the occurrence of CnRF ( 30 ), and timely restoration of MBF by eliminating these emboli is the cornerstone of alleviating myocardial injury and preserving cardiac functions.…”
Section: Discussionsupporting
confidence: 85%
“…More importantly, US+MB treatment decreased the percentage of microthrombi-occluded myocardial arterioles, as indicated by systemic histologic analysis of postmortem myocardium. These findings indicated that MB-mediated sonothrombolysis could efficiently dissolve coronary microthrombi, which is partially supported by previous in vivo and in vitro studies ( 20 22 , 29 ). Additionally, it is widely accepted that the burden of thrombotic microemboli is highly predictive of the occurrence of CnRF ( 30 ), and timely restoration of MBF by eliminating these emboli is the cornerstone of alleviating myocardial injury and preserving cardiac functions.…”
Section: Discussionsupporting
confidence: 85%
“…Petit et al (2015) observed a greater degree of rt-PA lysis with BR38 microbubbles exposed to 1 MHz pulsed ultrasound at an amplitude causing inertial cavitation (1.3 MPa peak rarefactional pressure) than at a lower amplitude causing stable cavitation (0.35 MPa peak rarefactional pressure). Goyal et al (2017) also measured a higher degree of thrombolysis with 1 MHz pulsed ultrasound at 1.0 MPa peak rarefactional pressure with inertial cavitation than at 0.23 MPa peak rarefactional pressure with stable cavitation in an in vitro model of microvascular obstruction using perfluorobutane-filled, lipid-shelled microbubbles (Weller et al 2002) as a nucleation agent. However, Kleven et al (2019) observed more than 60% fractional clot width loss for highly retracted human whole blood clots exposed to rt-PA, Definity and 220 kHz pulsed or continuous wave (CW) ultrasound at an acoustic output with sustained stable cavitation throughout the insonification periods (0.22 MPa peak rarefactional pressure) (Fig.…”
Section: Mechanisms Agents and Approachesmentioning
confidence: 93%
“…While fluorinated gases improve the stability of phospholipid-coated microbubbles (Rossi et al 2011), other gases can be loaded for therapeutic applications, such as oxygen for treatment of tumors (McEwan et al 2015;Fix et al 2018;Nesbitt et al 2018) and nitric oxide (Kim et al 2014;Sutton et al 2014) and hydrogen gas (He et al 2017) for treatment of cardiovascular disease. The main phospholipid component of custom-made microbubbles is usually a phosphatidylcholine such as 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), used in 13 studies (e.g., Dewitte et al 2015;Bae et al 2016;Chen et al 2016;Fu et al 2019), or 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), used in 18 studies (e.g., Kilroy et al 2014;Bioley et al 2015;Dong et al 2017;Goyal et al 2017;Pandit et al 2019). These phospholipids are popular because they are also the main components in Definity (Definity 2011) and SonoVue/Lumason (Lumason 2016), respectively.…”
Section: Cavitation Nuclei For Therapymentioning
confidence: 99%
“…Ultrasound (US) exposure of echocontrast agents has been investigated as an adjuvant to enhance rt-PA thrombolysis in previous in vitro 2226 , ex vivo 27 , and in vivo studies 2830 . Our group has reported enhanced thrombolysis in the presence of 120-kHz US with echogenic liposomes 31 .…”
Section: Introductionmentioning
confidence: 99%